ENGAGING YOUNG LEARNERS IN LEARNING VOCABULARY: A STUDY ON LEARNERS’ PERCEPTION - Tryanti R Abdulrahman; Muhammad Harris Jullian (Akademika, 2020)
This study examines students’ perception on the implementation of mobile games to engage young learners in learning English vocabulary. Thirty young learners in Islamic elementary school MI As-Syahid, Bekasi were the participant of the study. This qualitative study applied observation, survey, and interview. The findings revealed that: 1) young learners perceived that educational mobile games are effective in improving students’ activeness in learning and boost their motivation to learn vocabulary. 2) Young learners expand their vocabulary knowledge through mobile games, and.3) Learners have positive attitudes towards the use of educational mobile games as a supplementary medium of English learning. Additionally, mobile games can also be a potential tool to stimulate the motivation of children who experience failure in learning. This study contributes to the literature regarding vocabulary learning media and the use of mobile game in Indonesia. It highlights young learners’ perception of learning using mobile games.